EFFECT OF CUSCUTA REFLEXA STEM AND CALOTROPIS PROCERA LEAF EXTRACTS ON GLUCOSE TOLERANCE IN GLUCOSE-INDUCED HYPERGLYCEMIC RATS AND MICE - Rahmatullah, M.; Sultan, S.; Toma, T. T.; Lucky, Sayeda-a-Safa; Chowdhury, Majeedul H.; Haque, W. M.; Annay, Mst. Eashmat Ara; Jahan, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Cuscuta reflexa (whole plant) and Calotropis procera (leaves) are used in folk medicine of Bangladesh to control blood sugar in patients suffering from diabetes mellitus. The hypoglycemic effects of methanol and chloroform extracts of whole plants of Cuscuta reflexa, and methanol extract of leaves of Calotropis procera were investigated in oral glucose tolerance tests in Long Evans rats and Swiss albino mice, respectively. Both methanol and chloroform extracts of Cuscuta reflexa whole plant demonstrated significant oral hypoglycemic activity in glucose-loaded rats at doses of 50, 100 and 200 mg/kg body weight. The methanol extract of leaves of Calotropis procera, when tested at doses of 100 and 250 mg/kg body weight did not demonstrate any oral hypoglycemic effect when tested in glucose-loaded mice.